2016
DOI: 10.1620/tjem.239.263
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Biotin Metabolites Are Elevated in Hemodialysis Patients with Cramps

Abstract: Patients with renal failure undergoing hemodialysis (HD) are susceptible to muscle cramps during and after HD. Muscle cramps are defined as the sudden onset of a prolonged involuntary muscle contraction accompanied by severe pain. Through HD, water-soluble vitamins are drawn out with water. Since biotin, a water-soluble vitamin, plays an essential role as one of the coenzymes in producing energy, we have hypothesized that deficiency of biotin may be responsible for HD-associated cramps. We previously reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 8 publications
0
10
1
Order By: Relevance
“…46 This critical issue has pointed out who require hemodialysis from the analysis of patients’ blood for biotins. 47 Of notice is the specific detection of biotin by the Nafion-modified BDD electrode because the above biotin analogs are not oxidized at this applied potential for the oxidation of biotin. Apparently, the difference between the results obtained by the electrode and the immunoassay reflects the level of the biotin analogs.…”
Section: Resultsmentioning
confidence: 99%
“…46 This critical issue has pointed out who require hemodialysis from the analysis of patients’ blood for biotins. 47 Of notice is the specific detection of biotin by the Nafion-modified BDD electrode because the above biotin analogs are not oxidized at this applied potential for the oxidation of biotin. Apparently, the difference between the results obtained by the electrode and the immunoassay reflects the level of the biotin analogs.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty percent of HD patients under citrate dialysate (CD) would present HAMCs [5]. Despite palliative measures, no consistent effects have been obtained [6]. One of possible mechanisms of muscle cramps could be a disorder of muscle energy metabolism [4].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that limb ischemia during filtration is one of the causes of cramps. Hyponatremia causes vasoconstriction and decreased blood supply to the muscles and, in response to ischemia, it causes cramps and pain through pain stimulus factors such as histamine and bradykinin secretion (9). These painful muscle cramps often complicate hemodialysis, but their exact mechanism is unclear (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Hyponatremia causes vasoconstriction and decreased blood supply to the muscles and, in response to ischemia, it causes cramps and pain through pain stimulus factors such as histamine and bradykinin secretion (9). These painful muscle cramps often complicate hemodialysis, but their exact mechanism is unclear (8)(9)(10)(11). The results of a previous study showed that variables related to the hemodialysis process such as the round per minute (rpm) of pump, and the patient›s blood pressure and weight also affect the incidence of muscle cramps (12).…”
Section: Introductionmentioning
confidence: 99%